Diaspora identities, cosmopolitanism, and the promise of citizenship: Lusophony from the voices of musicians from African diasporas - Cidra, Rui (2022)
As a political category created in the second half of the 1990s to denote the relationships between Portugal and the nations linked to its colonial history, lusofonia has centrally mobilized popular music to imagine itself as a community. This article questions how African musicians and musicians descending from African diasporas in Portugal dwell within this category of lusofonia. It shows how musicians appropriate the concept according to different colonial, postcolonial, and diasporic trajectories and how these appropriations condense broader projects of identity, citizenship, and cosmopolitan ethics.